Commentary: “An Evaluation of Universal Grammar and the Phonological Mind”—UG Is Still a Viable Hypothesis - Berent, Iris (Frontiers in Psychology, 2016)
Everett (2016b) criticizes The Phonological Mind thesis (Berent, 2013a, 2013b) on logical, methodological and empirical grounds. Most of Everett’s concerns are directed towards the hypothesis that the phonological grammar is constrained by universal grammatical (UG) principles. Contrary to Everett’s logical challenges, here I show that the UG hypothesis is readily falsifiable, that universality is not inconsistent with innateness (Everett’s arguments to the contrary are rooted in a basic confusion of the UG phenotype and the genotype), and that its empirical evaluation does not require a full evolutionary account of language. A detailed analysis of one case study, the syllable hierarchy, presents a specific demonstration that people have knowledge of putatively universal principles that are unattested in their language and these principles are most likely linguistic in nature. Whether Universal Grammar exists remains unknown, but Everett’s arguments hardly undermine the viability of this hypothesis.